Detection and neutralization of venom by ovine antiserum in experimental envenoming by Bothrops jararaca - C. M. Peres; M. F. Bastos; J. Ferreira; A. Sartori (Journal of Venomous Animals and Toxins including Tropical Diseases, 2006)
In this study we optimized an enzyme-linked immunosorbent assay (ELISA) to evaluate bothropic venom levels in biological samples. These samples were obtained by two distinct protocols. In the first one, Swiss mice were injected with 1 LD50 of Bothrops jararaca (B. jararaca) venom and 15 minutes later, animals were treated with ovine antibothropic serum. Blood and spleen homogenate samples were obtained 6 hours after antiserum therapy. Ovine antibothropic serum significantly neutralized venom levels in serum and spleen. In the second protocol, BALB/c mice were injected with 1 LD50 of bothropic venom by either intraperitoneal (IP) or intradermal (ID) route and venom levels were evaluated 1, 3 and 6 hours after, in blood, spleen homogenates and urine. Serum and splenic venom levels were significantly higher in animals envenomed by IP route comparing with animals envenomed by ID route. Higher venom levels were also detected in urine samples from animals envenomed by IP route. However, these differences were not statistically significant. These results demonstrated that the optimized ELISA was adequate to quantify venom levels in different biological samples. This assay could, therefore, substitute the in vivo neutralizing assay and also be useful to evaluate the severity of human and experimental envenomations.